2020
DOI: 10.1109/access.2020.2980239
|View full text |Cite
|
Sign up to set email alerts
|

SDRE-Based Integral Sliding Mode Control for Wind Energy Conversion Systems

Abstract: This paper proposes a novel integral sliding mode control (ISMC) scheme based on numerically solving a state-dependent Ricatti equation (SDRE), nonlinear feedback control for wind energy conversion systems (WECSs) with permanent magnet synchronous generators (PMSGs). Unlike the conventional ISMC, the proposed control system is designed with nonlinear near optimal feedback control part to take into account nonlinearities of the WECSs. The Taylor series are used to approximate the solutions of SDRE. More specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…I rd − V rd . I rq (13) The power converter is an essential component for controlling the WECS. It is composed of two converters (AC/DC/AC) linked by a DC bus.…”
Section: Mathematical Modelling Of the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…I rd − V rd . I rq (13) The power converter is an essential component for controlling the WECS. It is composed of two converters (AC/DC/AC) linked by a DC bus.…”
Section: Mathematical Modelling Of the Systemmentioning
confidence: 99%
“…In [12] authors suggested sliding mode control. This technique deals very well with uncertainties and parameter variations to make the system more robust [13]. However, this latter is the origin of chattering phenomena [14].…”
Section: Introductionmentioning
confidence: 99%
“…In [19], a robust integraltype TSMC is suggested for grid-side converter of WECS with variable-speed PMSG. An integral SMC method based on numerical solution of a state-dependent Ricatti equation is suggested in [20] for nonlinear feedback control of WECSs with PMSGs. In [21], an adaptive SMC type-2 neuro-fuzzy approach is presented for speed-and power-regulation of DFIG.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Since the Lyapunov function time-derivative is negativedefinite, then, the Lyapunov function (20) gradually decreases and sliding surface s(t) is convergent to zero in finite time.…”
Section: Terminal Sliding Tracker Designmentioning
confidence: 99%
“…In order to combat these challenges nonlinear control methods based as sliding mode control (SMC), direct torque control (DTC), fuzzy control (FC), intelligent control (IC), model predictive control (MPC) have been designed for PMSG-based WECS. [18][19][20][21][22][23][24] Integral SMC has ability to eliminate reaching phase with LQR-based linear output feedback controller 19 and conventional state-dependent Riccatti equation (SDRE)-based nonlinear output controller 18 for guaranteeing closed-loop stability. The so-called chattering phenomenon in the sliding surfaces have been reduced by continuous approximation, but in Reference 21 second order SMC controller has been utilized to eliminate chattering.…”
Section: Introductionmentioning
confidence: 99%